PCR (Polymerase Chain Reaction) Method As A Detector of IMNV (Infectious myonecrosis virus) Disease in Vaname Shrimp (Litopenaeus vannamei) - Maharani, Dela Shinta; Sumsanto, Muhammad (Journal of Fish Health, 2024)
Indonesia is a maritime country that has great potential in the fisheries sector, especially in cultivating vaname shrimp (Litopenaeus vannamei). Disease in vaname shrimp is the biggest factor causing cultivation failure, one of which is caused by IMNV (Infectious myonecrosis virus). The aim of this research is to study IMNV detection techniques in vaname shrimp using the PCR (Polymerase Chain Reaction) method at the Situbondo Brackish Water Aquaculture Fisheries Center. This research uses a descriptive method, with stages starting from necropsy, RNA extraction using the silica method, amplification using RT-PCR and Nested-PCR, to electrophoresis and documenting the results using UV documentation. The results showed that the PCR technique was effective in detecting IMNV in shrimp, with DNA amplification clearly visible through agarose gel electrophoresis. Documentation of PCR results indicated the presence of a DNA band in the IMNV positive sample, which corresponded to the positive control. In conclusion, IMNV detection using the PCR method at BPBAP Situbondo has proven to be effective for identifying disease in vaname shrimp and can be applied as an initial step in controlling disease in vaname shrimp cultivation.